Formalizam za modeliranje poslovnog upravljanja javnom telekomunikacijskom mrežom : doktorski rad - Markulin, Darko; Kunštić, Marijan (Zagreb: D. Markulin ; Fakultet elektrotehnike i računarstva, 2014)
SAŽETAK: Kako je poslovno upravljanje vrlo složena okolina sustava, a postupci razvoja potrebne sistemske programske podrške vrlo složen postupak s velikom mogućnošću nastajanja pogreške nameće se potreba za modeliranjem njegovog ponašanja na učinkovit i jasan način. U radu je definiran jedan od mogućih načina modeliranja poslovnog upravljanja javnom telekomunikacijskom mrežom u sklopu postojećeg razvoja poslovnih procesa i sistemske programske podrške. Primjenom odabranih formalnih metoda i jezika definiran je model koji uspješno predstavlja i simulira funkcije poslovnog upravljanja javnom telekomunikacijskom mrežom. Time model predstavlja dovoljnu izražajnu snagu za izradu specifikacije na temelju koje se može pristupiti implementaciji stvarne sistemske programske podrške. Primjenom metode objedinjavanja iskustvenog znanja definirala se sintaksa i semantika grafičkog formalnog modela kojim se oblikuje poslovno upravljanje javnom telekomunikacijskom mrežom. Pri tome su razmotrene različite formalne metode koje omogućavaju vizualno modeliranje sustava te ostale metode koje se koriste u modeliranju poslovnih procesa i sustava upravljanja tijekom poslova. Predstavljeno je programsko rješenje uz pomoć kojeg je moguća simulacija dinamičkog ponašanja poslovnog upravljanja kroz definirani formalni model. Naglašeno je da odabir jedne od postojećih formalnih metoda za izradu formalnog modela nije dovoljna za izradu modela koji uspješno zadovoljava potrebe za modeliranjem javne telekomunikacijske mreže, već je potrebna kombinacija različitih metoda uz pomoć korištenja iskustvenog znanja. Definirani formalni model je primijenjen na modeliranje potrebnih procesa za uključenje VoIP usluge u javnoj telekomunikacijskoj mreži. Model omogućuje vizualni i pregledni prikaz potrebnih promjena u sustavu za upravljanjem tijekom poslova i potrebnih podataka koje taj sustav izmjenjuje sa svojom programskom okolinom. Odvijanje poslovnih procesa simulirano je uz pomoć formalnog modela i na temelju definiranih scenarija u izvođenju poslovnih procesa. Na temelju dobivenih rezultata zaključeno je da se model može uspješno koristiti u svrhu modeliranja sistemske programske podrške koja se koristi u javnoj telekomunikacijskoj mreži. - KLJUČNE RIJEČI: modeliranje, specifikacija, sistemska programska podrška poslovnog upravljanja, iskustveno znanje, formalni dijagrami, simulacija
SUMMARY: Business management is a very complex system environment and the development of required business management is a very complex procedure with a high possibility of the error occurrence. Therefore there is a need for the modelling its behaviour in an efficient and transparent manner. It certainly opens up a space for the application of formal methods in specifying required system properties. Formal methods are based on the mathematical models that have defined its syntax and semantics, and therefore can describe system behaviour in a precise and unambiguous way. The purpose of this dissertation was to prove the hypothesis about the need for using formalism in the phase of specifying required business management in introducing or optimizing the use of telecommunication services in the public telecommunications network. During the desired model definition the method of integrating experiential knowledge was used. Experiential knowledge was based on active participation in the current process of developing specifications and modelling of business processes which make business management needed for connection or change in telecommunications service. Furthermore, experiential knowledge was based on all noted problems and faults that want to eliminate or mitigate and thus confirm the hypothesis of the need for the application of formalism in the early stages of the design of business processes. Dissertation defines one of the possible ways of modelling business management of a public telecommunications network within the existing development of the business processes and system support. A model that successfully represents and simulates functions of business management of a public telecommunications network was defined by application of selected formal methods and languages. Thus model represents a sufficient expressive power to produce specifications which can be the base for the implementation of a real system support. The first chapter describes business management of the telecommunications network from the perspective of the concept of TMN network management and a special focus was given to the workflow management system. The second chapter describes development phases of the system support. The basic elements of the model for description of the workflow management system are defined. These elements are needed for the system dynamic behaviour modelling. The third chapter provides an overview of the formal methods features and describes these methods based on the diagrams. Requirements which a formal diagram has to satisfy in business management modelling are set out. The fourth chapter gives an overview of the way system support modelling with the help of non-standardized diagrams and results and models presentations obtained by using selected formal methods. The fifth chapter presents the results validity tests of a formal model and discusses the obtained results. An appendix 1 describes the software tool that was applied in the creation of a formal model. Existing software tool ActiveCharts was used with the application of the program code and its application was adapted to the needs of business management modelling. An appendix 2 shows an example of the business support modelling with the help of the elements of UML2 activity diagrams and a formal model of the public telecommunications network business management. In an appendix 3 there are listed scenarios for validation and verification of the business management formal model as well as defined functionalities which have to be covered through the scenarios. An appendix 4 shows business management simulation result for one of the provided scenarios. An appendix 5 gives representation of the performance simulation of the selected more complex part of the business process. The syntax and semantics of the graphical formal model which shapes business management of the public telecommunications network are defined by using the method of the experiential knowledge. Thereby, various formal methods that allow visual modelling of the system are considered. A software solution that could make the simulation of business management dynamic behaviour through a defined formal model possible is presented. It points out that the selection of one of the existing formal methods for the preparation of a formal model is not sufficient to create a model that successfully meets the needs for modelling the public telecommunications network. Therefore, it is necessary to combine different methods using experiential knowledge. Simulation is used as a practical alternative to verification. A technique of testing models through the possible predefined scenarios of business processes execution is used for specification assessment. Although, unlike complete verification, simulation can reveal error occurrence, but cannot prove discovery of all the errors, it is practical and valuable alternative to verification, which is very cost and time demanding procedure. Simulation allows testing model properties that are not clearly visible from the sole specifications. Thus, it is possible within every scenario to go into different parts of the process according to the defined parameters and validate model accuracy in relation to this scenario, which at the same time represents the business case that can occur within the provision of telecommunications services. A defined formal model is applied to the modelling of the processes needed for the connection of the VoIP services in the public telecommunications network. The model provides a visual and easy overview of the necessary changes in the workflow management system and information which this system exchanges with its programming environment. Business processes are simulated by a formal model, based on defined scenarios in business processes execution. Based on the results, it could be concluded that this model can be successfully used for the modelling the system support which has been used in the public telecommunications network. - KEY WORDS: modelling, specification, system program support for business management, experiential knowledge, formal diagram, simulation
Na spor. nasl. str. naslov na eng. jeziku: Formalism for modelling business management of public telecommunication network : doctoral thesis
Bibliografija: str. 94 - 96. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje i popis radova autora]